When corporate parenting aids strategic clarity: The importance of a firm's core competencies. Issue 9 (9th September 2019) - Unknown
Abstract : Purpose: This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: Many firms today opt to seek growth through a diversification strategy. Success becomes likelier when the company is able to access key resources and capabilities and adopts a corporate parenting approach that is both appropriate and highly focused. Originality/value: The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.